(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the ways in which oral folk traditions are integrated into the fairy tales of Alexander Sergeyevich Pushkin, focusing on folkloric elements such as archetypes, plot structures, and stylistic features, and their role in creating a unique literary form. Particular attention is given to how Pushkin employs traditional motifs and images to convey ideas of justice, morality, and social order, characteristic of folk narratives. The work also analyzes how oral traditions are transformed within the context of Pushkin’s authorial text, acquiring new artistic and ideological meanings.